Review of "Lingua e diritto. Livelli di analisi" by Jacqueline Visconti (ed.). Milano, LED Edizioni universitarie 2010 - Sočanac, Lelija (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2011)
The book Lingua e diritto. Livelli di analisi brings together contributions by scholars from different fields: anthropology, theory and philosophy of law, comparative law, European law, translation, discourse analysis, pragmatics, morpho-syntax and cognitive linguistics. Contributions deal with a number of issues situated at the interface between language and law: questions of meaning and the interpretation of legal texts, the nature of legal interpretation, problems of ambiguity and vagueness in legal texts, the characteristics of legal language, legal terminology and the multilingualism of European law. As a whole, the book provides insights into a number of different topics and perspectives situated at the interface between language and law. It is of interest both to lawyers and linguists as a valuable and very welcome contribution to the field of legal linguistics. Der Sammelband Lingua e diritto. Livelli di analisi vereinigt Beiträge von Wissenschaftlern ganz unterschiedlicher Fachrichtungen: Anthropologie, Rechtstheorie und –philosophie, Vergleichende und Europäische Rechtswissenschaft, sowie Übersetzungswissenschaft, Diskursanalyse, Pragmatik, Morphosyntax und Kognitive Linguistik. Die Beiträge beschäftigen sich mit einer Vielzahl von Aspekten an der Schnittstelle zwischen Sprache und Recht: Fragen der Bedeutung und der Auslegung von Rechtstexten, dem Wesen der Rechtsauslegung, Problemen von Mehrdeutigkeit und Vagheit in Rechtstexten, Merkmalen der Rechtssprache, Rechtsterminologie und der Mehrsprachigkeit im Europarecht. Insgesamt liefert das Buch Einblicke in eine Vielzahl von Themengebieten und Perspektiven im Spannungsfeld von Sprache und Recht und ist damit ein wertvoller und sehr willkommener Beitrag sowohl für Rechts- als auch für Sprachwissenschaftler im Bereich der Rechtslinguistik.
Keywords: Rezension; Sprache und Recht; EU; Rechtstexte; Rechtslinguistik